Hypoxia and exercise (Advances in Experimental Medicine and Biology, 2006)
The 14th volume in the series will focus on cutting edge research at the interface of hypoxia and exercise. The work will cover the range from molecular mechanisms of muscle fatigue and muscle wasting to whole body exercise on the world`s highest mountains. State of the art papers on training at high altitude for low altitude athletic performance will also be featured.